Boiler maintenance using expert systems - Gamede, Cyril Vuyani (Department of Mechanical Engineering, 2016)
This research explores the application of expert systems to the maintenance of boilers, are as follows: and its main objectives [1] To explore the application of expert systems in the maintenance of boilers. [2] To simplify the task of boiler maintenance with the help of expert systems. [3] To improve the skills of boiler maintenance workers through the knowledge 'captured ' or 'preserved' by expert systems. [4] To minimise errors which may cost time, money, effort and possible risk of injury to boiler maintenance personnel. [5] To develop a prototype expert system which can advise and assist boiler maintenance personnel. [6) To contribute to research in the application of expert systems in the field of engineering.